Political Meaning-Making In Indonesian Presidential Debates: A Systematic Review Of Multimodal Discourse Analysis - Sinaga, Yanti Kristina; Fithriani, Rahmah; Pardi , Pardi (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Political debates are critical sites of meaning-making in democratic elections, where candidates communicate policies, values, and leadership personas through multiple semiotic modes. This study systematically reviews research on multimodal discourse analysis (MDA) of Indonesian presidential debates published between 2020 and 2025, aiming to synthesize theoretical frameworks, analytical practices, and thematic patterns in political communication. Using a structured systematic literature review, peer-reviewed journal articles, conference proceedings, and book chapters were collected from Scopus, Web of Science, Google Scholar, and DOAJ. Studies were screened based on their relevance to Indonesian presidential debates, use of multimodal frameworks, and empirical rigor. The review revealed that social semiotics is the predominant theoretical framework, with verbal language, gesture, and facial expressions being the most analyzed semiotic modes. Dominant themes of political meaning-making include leadership construction, national identity and populist appeals, and interactional power negotiation, often mediated by televised and digital platforms. While multimodality enhances understanding of how meaning is co-constructed, methodological inconsistencies—including small datasets and variable transcription practices—limit comparability across studies. This review highlights the growing importance of multimodal approaches for analyzing political debates in Indonesia and identifies gaps for future research. Specifically, more balanced attention to underexplored semiotic modes, standardized transcription methods, and theoretical integration are needed to advance the field. The study contributes to political discourse research by providing a comprehensive synthesis of recent multimodal analyses, offering insights into the complex ways in which Indonesian presidential candidates communicate meaning to diverse audiences.